The transcription factor RhMYB17 regulates the homeotic transformation of floral organs in rose (Rosa hybrida) under cold stress - Yang, Tuo (Journal of experimental botany, 2024)
© The Author(s) 2024. Published by Oxford University Press on behalf of the Society for Experimental Biology.